MYASTHENIA GRAVIS WITH FEATURES OF ACUTE PONS INFARCTION: A RARE CASE REPORT - Kencana Dewi, Ni Luh Diah; Arimbawa, I Komang; Dwita Pratiwi, Ni Made (MNJ (Malang Neurology Journal), 2024)
Background: Myasthenia gravis (MG) is an antibody-mediated autoimmune disease at neuromuscular synaptic transmission. The clinical sign of a myasthenia gravis is the presence of weakness that affects vision (ocular), bulbar and proximal skeletal muscles and also myasthenia gravis can resemble vascular disorders or any infectious diseases. Case: A 48-year-old Balinese male patient came to the emergency department of  Prof I.G.N.G Ngoerah Central General Hospital complaining of shortness of breath. Shortness of breath is said to have occurred since one month ago. Shortness of breath improves slightly when the patient rests. Another complaint felt by the patient is that the right eyelid drops, especially during the daytime, will improve in the afternoon. The patient denied any weight loss or a history of malignancy. The patient about three months ago had fallen from a motorcycle and felt numbness in his right cheek until now. The patient has been undergoing treatment at the District General Hospital and he was diagnosed with myasthenia gravis and took Mestinon. CT scan of the head showed an acute infarction of the left pons accompanied by a suspicion of acute meningoencephalitis. Discussion: From the results of the RNS (Repetitive nerve stimulation) in this patient, it was found that the neuromuscular junction lesion was supportive of the description of the myasthenia gravis case. Conclusion: Myasthenia gravis is a disease of the nervous system with various manifestations. Good clinical examination and supporting examination are very necessary to confirm the diagnosis.